Существует ли необходимость в гипотезе универсального генома? - Михеев, А.Н. (Фактори експериментальної еволюції організмів, 2014)
On the example of hypothesis about the «universal genome» of M. Sherman important questions in relation to the rates (speeds) of evolutional transformations of the biological systems and problem of abundance (inertness) of evolutional transformations are considered in the article. Geological, ecological and biological mechanisms which explain the phenomenon of the Cambrian explosion are selected. It is demonstrated that hypothesis of “universal genome” of not contradicts to modern evolutional views.

Key words: hypothesis about the «universal genome», evolutional transformations of the biological systems, phenomenon of the Cambrian explosion.